Red Sandstones From the Holy Cross Mountains Region in the Historic and Contemporary Architecture of Warsaw (Poland) - Bobrowska Alicja; Ewa Jagoda (Geoheritage, 2026)
In Warsaw’s architecture, numerous historic and contemporary structures feature cherry-colored Triassic sandstones originating from Tumlin, Suchedniów, and Wąchock in the Holy Cross Mountains (Świętokrzyskie) region of Poland. This paper presents selected important examples of their use in the Warsaw city, based on archival sources, earlier publications, and systematic observations. The documentation is supplemented with geomechanical data on the physical and mechanical properties of these sandstones, obtained from laboratory analyses at the Geomechanics Laboratory of the University of Warsaw.